Zabawy dzieci w różnych kulturach – perspektywa antropologiczno-pedagogiczna - Urszula Markowska-Manista (Problemy Wczesnej Edukacji)
The text refers to contemporary interdisciplinary research on children’s play in different cultures. The author reflects on the diverse functions of play in the context of the multiplicity of childhoods and in view of the changing conditions and contexts of children’s lives, as well as the changing models of childhood and the ways and possibilities of children’s functioning in the 21st century. New global processes and transformations, in which children are the most numerous group of participants, enable a broader insight into their situation and, above all, into play and toys – tools with which they recognize, encode and learn about the surrounding world.